2021
DOI: 10.4314/tjs.v47i3.20
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Endophytic Fungal Crude Extracts Isolated from Cashew Tree (Anacardium occidentale)

Abstract: This study presents the antimicrobial activities of endophytic fungal crude extracts isolated from leaves, stems and roots of cashew trees (Anacardium occidentale) which showed disease symptoms and those resistant from Fusarium wilt in Mtwara region. Sections of the cashew trees were made and cultured to isolate endophytes. Eight endophytes were isolated and characterized by using morphological and molecular markers. Neopestalotiopsis, Penicillium, Lasidioplodia and Daldinia sp isolated from resistant tree and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…Reports on Cryptosporiopsis, which causes cashew blight disease infecting mainly the apple and nuts, were restricted to Tanzania (n = 8), with a high potential to decrease cashew productivity [47]. The Fusarium genus represented by a single species (F. oxysporum) was associated with root rot disease [63] and, more recently, with Fusarium wilt disease (FWD) in Tanzania [15], which mainly affects the leaf and root/stem and ultimately leads to complete wilting of the cashew canopy and tree death [64]. Our study showed that F. oxysporum occurs in Tanzania (East Africa), Nigeria (West Africa), India, and Indonesia.…”
Section: Other Fungal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on Cryptosporiopsis, which causes cashew blight disease infecting mainly the apple and nuts, were restricted to Tanzania (n = 8), with a high potential to decrease cashew productivity [47]. The Fusarium genus represented by a single species (F. oxysporum) was associated with root rot disease [63] and, more recently, with Fusarium wilt disease (FWD) in Tanzania [15], which mainly affects the leaf and root/stem and ultimately leads to complete wilting of the cashew canopy and tree death [64]. Our study showed that F. oxysporum occurs in Tanzania (East Africa), Nigeria (West Africa), India, and Indonesia.…”
Section: Other Fungal Diseasesmentioning
confidence: 99%
“…Despite previous reports of root rot disease in Nigeria in 1974 [65] and afterward in Indonesia [63] and India [66], few studies highlighted F. oxysporum as a major pathogen in cashew. Nevertheless, due to the alarming scenario described in recent works from Tanzania [64], where cashew orchards have been devastated by FWD, cashew-producing countries should be vigilant regarding possible future infections by this pathogen. Indeed, due to the lack of proper disease-screening trials in cashew-producing countries, Fusarium should not be discarded as a minor pathogen and remains to be identified at the species level.…”
Section: Other Fungal Diseasesmentioning
confidence: 99%